Research on wheel-rail noise in rail corrugation road of urban rail transit - Huang, Chunlin; Zhang, Xiaoan (E3S web of conferences, 2024)
As an efficient, fast, green and environmentally friendly means of transportation, subway vehicles account for the largest proportion of urban rail transit, and in large and medium-sized cities, the construction of subway is still in rapid development, but with the subway noise radiation problem, subway noise plagued by passengers, related operators and residents along the subway. In this study, the finite element analysis software ABAQUS is used to establish the coupled dynamics model of subway B-type vehicle-rail, and the acoustic radiation characteristics of wheels and rails are calculated based on the FE-BE and FE-SEA method, respectively, with the aim of analyzing the effects of different wavelength and depth parameters on the dynamics of vehicle response and wheel-rail noise radiation pattern when the vehicle is running on the rail corrugation road. The results of the study show that the effect of rail corrugation parameters on the power level of wheel and rail sound radiation is more significant in the low-frequency range, and the wheel-rail noise is mainly radiated by the wheel in the low-frequency range, while in the high-frequency range, it is mainly radiated by the rail.